Rules and Procedures for an External Audit of Financial Statements in Ecuador - Mancheno-Vaca, Carlos (2015)
The Audit has become an ally of companies and entrepreneurs to possible sources of financial distortion such as labor and corporate fraud that carry a high risk for information users such as: investors, shareholders, internal or external customers, suppliers and the State, on this basis the organizations hire both internal and external Auditors who must meet certain fundamental requirements such as experience, independence, confidentiality and integrity; In the face of possible fraud, those who would be responsible for permanently monitoring departures from the organization's economic operations are the internal auditors, since their position is to monitor internal control and existing risks, timely reporting on situations such as hockey, Of funds, over and underestimation of assets and liabilities, among others. The scope of an external audit is different since its focus and objective is to express an opinion on the reasonableness of balances and compliance with principles and rules governing accounting and financial application in companies, issuing reports that must be presented to Control agencies such as the Superintendency of Companies and the Internal Revenue Service.